Distribución de Solanáceas Cultivables en el Ecuador para mejorar la Vigilancia Fitosanitaria de Plagas y Enfermedades. - Marcalla González, Francis Lorena (2020)
Currently, potato purple tip is affecting potato producers in Ecuador. Potential causal agents of purple top are affecting other crops such as tomatoes, peppers, eggplants, grapes, tree tomatoes, tobacco, and various weeds of the Solanaceae family. However, until this moment, there has not been an active surveillance system for the possible causal agents that produce potato purple tip syndrome. This research aimed to determine the distribution of Solanaceae to help improve monitoring systems in Ecuador. To answer this research question, historical databases were downloaded from the official website of the Surface and Continuous Agricultural Production Surveys (ESPAC). The database corresponds to the surveys conducted from 2012 to 2018. These databases were compiled taking into account the variables: (1) indicator, (2) province, (3) parish, (4) crop code, (5) area planted, and (6) total land area. Within these data, only the information corresponding to host crops of C. liberibacter solanacearum or the psyllid Bactericera cockerelli was selected. The following solanaceous crops were selected: tree tomato, grapevine, eggplant, potato, bell pepper, chili, kidney tomato and Andean crops such as mashua and melloco, giving a total of 9 crops. With this information, an index was created to determine the diversity of solanaceous plants in Ecuador. The database created was linked to the GIS files of the National Institute of Statistics and Census of Ecuador (INEC), in order to make distribution maps of each of the crops mentioned. The results of this research showed that the northern zone of Ecuadorian territory is the one with the highest diversity of solanaceous plants reported by farmers and that of the 9 crops considered in the research, not all are hosts of C. liberibacter solanacearum or the psyllid Bactericera cockerelli. It is expected that the results obtained in this research will contribute to design phytosanitary surveillance systems for purple tip both in potato and other solanaceous crops grown in Ecuador and other crops that are hosts of various pests.